2021
DOI: 10.46328/ijemst.1446
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Graduate Students’ Technological Pedagogical and Content Knowledge (TPACK)

Abstract: This study aimed to investigate and compare the perception of TPACK competence of graduate students studying at the institutes of Natural Sciences, Social Sciences and Educational Sciences based on the variables of gender, graduate program level and field. The participants of the research consist of 186 graduate students studying at the institutes of Karatay, Necmettin Erbakan and Selçuk University. TPACK Competence Scale was used to collect research data. The results of the research showed that graduate stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
2
7
0
2
Order By: Relevance
“…According to the regression analysis, both pedagogical competence and technological competence, separately and together, significantly affect the differentiated teaching self-efficacy of the participants. These findings are supported by the results of studies conducted by Finley (2008), Koyuncuoğlu (2021), andWelsh (2010). A high level of positive correlation has emerged between the levels of foreign language teacher candidates' levels of applying differentiated instruction according to current conditions and their competency levels.…”
Section: Discussionsupporting
confidence: 70%
“…According to the regression analysis, both pedagogical competence and technological competence, separately and together, significantly affect the differentiated teaching self-efficacy of the participants. These findings are supported by the results of studies conducted by Finley (2008), Koyuncuoğlu (2021), andWelsh (2010). A high level of positive correlation has emerged between the levels of foreign language teacher candidates' levels of applying differentiated instruction according to current conditions and their competency levels.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, the TPACK framework is useful for the ways in which it explicates the types of knowledge most needed in order to make technology integration successful in the classroom. Teachers need not even be familiar with the entire TPACK framework as such in order to benefit from it: they simply need to understand that instructional practices are best shaped by content-driven, pedagogically-sound, and technologically-forward thinking knowledge (Al-Abdullatif, 2019;Hsu et al;Koyuncuoglu, 2021;Lee, Smith, & Bos, 2014).…”
Section: Kara 528mentioning
confidence: 99%
“…At the end of the study, they reported that there was a statistically significant difference gap between first-year and fourth-year students in relation to their TPACK competencies. In a recent survey, Koyuncuoğlu (2021) examined the TPACK perceptions of 186 graduate students based on some variables in Turkey and found a significant difference among the mean scores of PK, CK, and TCK by education level. He also reported that the mean PK, CK, and TCK scores of the doctoral students were significantly greater than those of the master's students.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Altun (2019) examined the TPACK competencies of 481 preservice early childhood teachers and reported no statistically significant differences among the pre-service teachers' TPACK scores in relation to their grade level. Similarly, Koyuncuoğlu (2021) declared that there was no significant difference in the mean TK, PCK, TPK, and TPACK scores based on the graduate education program. Through a cross-sectional design, Turgut (2017) investigated 174 Turkish pre-service teachers' self-perceived TPACK and she also reported that there was no significant gap between fourth-year and second-year students related to TK, TCK, TPK, and TPACK.…”
Section: Introductionmentioning
confidence: 99%